b - WHO Expert Committee on Specifications for Pharmaceutical Preparations; World Health Organization (Geneva : World Health Organization, 1990)
Considers questions concerning the quality assurance of pharmaceuticals and specifications for drug substances and dosage forms. Technical issues discussed include drug stability and sampling procedures, the problems created by falsely labelled, spurious, counterfeited, and substandard preparations, and the corresponding need for appropriate preventive measures in both importing and exporting countries. Other topics include the further development of the International Pharmacopoeia, the establishment of international chemical reference substances, and developments in the WHO Certification Scheme on the Quality of Pharmaceutical Products Moving in International Commerce. Annexed to the report is a document outlining guiding principles for small national drug regulatory authorities.